Adipokines, Biomarkers of Endothelial Activation, and Metabolic Syndrome in Patients with Ankylosing Spondylitis. (17th March 2014) - Genre, Fernanda; López-Mejías, Raquel; Miranda-Filloy, José A.; Ubilla, Begoña; Carnero-López, Beatriz; Blanco, Ricardo; Pina, Trinitario; González-Juanatey, Carlos; Llorca, Javier; González-Gay, Miguel A.
Abstract : Ankylosing spondylitis (AS) is a chronic inflammatory rheumatic disease associated with accelerated atherosclerosis and increased risk of cardiovascular (CV) disease. AS patients also display a high prevalence of features clustered under the name of metabolic syndrome (MeS). Anti-TNF- α therapy was found to be effective to treat AS patients by suppressing inflammation and also improving endothelial function. Previously, it was demonstrated that a short infusion of anti-TNF- α monoclonal antibodyinfliximab induced a rapid and dramatic reduction in serum insulin levels and insulin resistance along with a rapid improvement of insulin sensitivity in nondiabetic AS patients. The role of adipokines, MeS-related biomarkers and biomarkers of endothelial cell activation and inflammation seem to be relevant in different chronic inflammatory diseases. However, its implication in AS has not been fully established. Therefore, in this review we summarize the recent advances in the study of the involvement of these molecules in CV disease or MeS in AS. The assessment of adipokines and biomarkers of endothelial cell activation and MeS may be of potential relevance in the stratification of the CV risk of patients with AS.